ENHANCING STUDENTS’ SCIENTIFIC REASONING USING INQUIRY-BASED LEARNING WITH COMPUTER SIMULATION - Nugraha, Muhamad Gina; Kirana, Kartika Hajar; Sholihat, Fitri Nurul; Janeusse, Nuzulira; Amalia, Shita Ayu (Jurnal Pengajaran Matematika dan Ilmu Pengetahuan Alam, 2017)
Physics education has long emphasized the importance of developing students’ scientific reasoning. This study investigated the development of students’ scientific reasoning using inquiry-based learning with computer simulation. Students’ scientific reasoning was probed by Lawson Classroom Test of Scientific Reasoning (LCTSR) and questionnaire to explore students’ response to the learning strategy. Results showed that all of six scientific reasoning aspects (material and volume conservation, proportional thinking, variable identification and control, probabilistic thinking, correlative thinking, and hypothetic-deductive thinking) was enhanced after learning with average N-Gain reflected the results. Aside from scientific reasoning enhancement, students responded positively to the learning strategy.